2018
DOI: 10.1016/j.canlet.2018.09.022
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting LRP8 inhibits breast cancer stem cells in triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is the most difficult subtype of breast cancer to treat due to a paucity of effective targeted therapies. Many studies have reported that breast cancer stem cells (BCSCs) are enriched in TNBC and are responsible for chemoresistance and metastasis. In this study, we identify LRP8 as a novel positive regulator of BCSCs in TNBC. LRP8 is highly expressed in TNBC compared to other breast cancer subtypes and its genomic locus is amplified in 24% of TNBC tumors. Knockdown of LRP8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 74 publications
2
26
0
Order By: Relevance
“…In our study, we found that ITGA9 downregulation promotes β‐catenin degradation, which may provide an alternative strategy for inhibiting β‐catenin pathway through targeting ITGA9. Indeed, ours and other recent studies provided additional support to this idea of targeting abnormally expressed or activated molecules in cancer cells that enhance β‐catenin signaling to reduce TNBC stemness, tumor growth and metastasis …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In our study, we found that ITGA9 downregulation promotes β‐catenin degradation, which may provide an alternative strategy for inhibiting β‐catenin pathway through targeting ITGA9. Indeed, ours and other recent studies provided additional support to this idea of targeting abnormally expressed or activated molecules in cancer cells that enhance β‐catenin signaling to reduce TNBC stemness, tumor growth and metastasis …”
Section: Discussionsupporting
confidence: 59%
“…Indeed, ours and other recent studies provided additional support to this idea of targeting abnormally expressed or activated molecules in cancer cells that enhance β-catenin signaling to reduce TNBC stemness, tumor growth and metastasis. 49,50 In summary, the findings from this study not only shed new light on TNBC biology and also reveal novel therapeutic opportunities with the potential to improve clinical outcomes of TNBC by targeting ITGA9.…”
Section: Discussionmentioning
confidence: 82%
“…Intriguingly, we observed a reversion of APA events occurred after CPSF1 or PABPN1 knockdown. The involved genes participate in drug resistance ( SCL9A1 38 , CCSAP 54 , NUP98 55 , PLD1 56 ), tumorigenesis ( DEPDC5 57 ), proliferation ( MED15 58 , STX3 59 ) and metastasis ( ARHGEF26 60 , ATP6V0A2 61 , MBD4 62 ) in breast cancer and are breast cancer biomarkers ( ITPR1 63 , NUP98 55 , GATA3 64 , 65 , DOCK4 66 , OSR1 67 ) and potential drug targets for TNBC ( SCL9A1 38 , LRP8 68 , 69 ). It suggests understanding APA regulation mediated by the core 3' processing factors, especially the target specificity and directionality, may provide new ideas for targeted therapy in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…The function of LRP8/ApoER2, strongly expressed in ER negative breast tumors was recently described in breast tumor initiating cells, which constitute a clinical challenge of the pathology ( 18 ). Interestingly, its depletion impairs TNBC cell proliferation and promotes apoptosis ( 19 ).…”
Section: Lrps and Breast Cancer Cells: A Close And Complex Relationshmentioning
confidence: 99%
“…Interestingly, its depletion impairs TNBC cell proliferation and promotes apoptosis ( 19 ). LRP8 depletion also leads to Wnt/β-catenin signaling inhibition, decreases the pool of BC cells, limits their tumorigenic potential in murine xenografts, and finally restores TNBC cell sensitivity to chemotherapy ( 18 ). An overview of the complex and multiple LRPs-mediated signaling pathways is shown in Figure 1 .…”
Section: Lrps and Breast Cancer Cells: A Close And Complex Relationshmentioning
confidence: 99%